High Calorie Diet and the Human Brain Metabolic Consequences of Long-Term Consumption - Farooqui, Akhlaq A. (Springer International Publishing : Imprint: Springer, 2015)
This monograph presents readers with cutting edge and comprehensive information on the effect of long term consumption of a high calorie diet on visceral organs and brain. It is the first monograph to describe the effect of macronutrients (carbohydrates, fats, and protein), table salt, and fiber (high calorie diet) on neurochemical processes related inflammation and oxidative stress in the brain. It will be useful to postgraduate students, faculty, research scientists, nutritionists, and physicians, who are curious about alterations in signal transduction processes due to long term consumption of high calorie diet. Healthy diet is an important component of good health. Long term consumption of a high calorie diet promotes insulin resistance, obesity, type II diabetes, and metabolic syndrome. The later is an important risk factor for stroke, Alzheimer disease, and depression. In contrast, the long term consumption of Mediterranean Diet reduces the risk of obesity, type II diabetes, and metabolic syndrome. A healthy lifestyle-which includes a healthy diet with plenty of fruits, vegetables, beans, fish, less red meat; moderate exercise for maintaining a healthy body weight; and optimal sleep may help in preventing not only diabetes, and metabolic syndrome, but delaying the pathogenesis of stroke, Alzheimer disease, and depression.